Inelastic, exchange, and reactive processes in rovibrationally excited collisions of HD with H. Issue 4 (16th September 2021) - Zhou, Boyi; Yang, Benhui; Balakrishnan, N; Kendrick, B K; Chen, Maodu; Stancil, P C
ABSTRACT: The HD molecule is an important coolant in early universe chemistry models and a tracer of H2 in star-forming regions. Rate coefficients for collisional excitation and de-excitation of HD rotational and vibrational levels form important ingredients in astrophysical models. While collisions with He, H2, and H are the most important, available data for H + HD collisions are largely limited to temperatures less than 1000 K for the vibrational ground state, low-lying rotational levels of the v  = 1 HD vibrational level, or computed without reactive contributions. Here, through explicit quantum scattering calculations, we report extensive data for rovibrational transitions in HD induced by H atoms for a range of rotational levels in v  = 1 and some v  = 0 levels for temperatures up to 1000 K. The significance of the computed results for astrophysical modeling is discussed.